FORENSIC LINGUISTIC EXAMINATION OF REGIONALLY MARKED UNITS IN UZBEK PERSONAL CORRESPONDENCE - Turayeva Dildora Anvarovna (International Journal of Literature and Language Studies, 2026)
Discusses dialectal meanings, dialectal taxonomy, areal contactology, regionally marked and unmarked units and the methodology of forensic analysis. It emphasizes conducting syntactic, grammatical, phonetic and lexical examinations to identify regionally marked units.